2022
DOI: 10.1111/ggi.14457
|View full text |Cite
|
Sign up to set email alerts
|

Strength and morphology of a suprahyoid muscle and their relationship to forward head posture in healthy older adults

Abstract: Forward head posture, an abnormality in head and trunk positioning, adversely affects suprahyoid muscle activity. Jaw-opening force, which reflects suprahyoid muscle strength, is a useful index of dysphagia. However, the relationship between forward head posture and strength and morphology of suprahyoid muscles remains unclear. This study aims to clarify the relationship between forward head posture, jaw-opening force and morphology of suprahyoid muscles.Methods: During October 2018, we enrolled older adults a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Anterior head posture has been reported to affect the activity of the supraorbital muscles 11) ; therefore, it is necessary to consider structural changes in the neck, in addition to the kyphosis condition. Tamai et al 12) reported that the cross-sectional area and transverse diameter of the geniohyoid muscles decreased with an anterior head posture, and this posture was also associated with an opening force proportional to the action of the suprasellar muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior head posture has been reported to affect the activity of the supraorbital muscles 11) ; therefore, it is necessary to consider structural changes in the neck, in addition to the kyphosis condition. Tamai et al 12) reported that the cross-sectional area and transverse diameter of the geniohyoid muscles decreased with an anterior head posture, and this posture was also associated with an opening force proportional to the action of the suprasellar muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the hyoid bone position is easily affected by posture and head position. Anatomically, the GHM and tongue are connected to the hyoid bone; therefore, a forward head posture increases the GHM length 15 and affects tongue position and morphology. When the mandibular bone is advanced by orthognathic surgery in patients with malocclusion, the length of the GHM increases significantly, and the CSA is greatly reduced compared to its preoperative state 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The trunk muscles are associated with kyphosis severity 13 , wherein severe kyphosis leads to a forward head posture. The association between dysphagia and kyphosis has been reported 14 ; the more severe the forward head posture, the longer the GHM, and the longer the GHM, the lower the jaw opening force 15 . Morphological features are also related to muscle strength in swallowing-related muscles 3 .…”
Section: Introductionmentioning
confidence: 99%